Emergent antibacterial activity of N-(thiazol-2-yl)benzenesulfonamides in conjunction with cell-penetrating octaarginine. Issue 46 (25th August 2021) - Ratrey, Poonam; Das Mahapatra, Amarjyoti; Pandit, Shiny; Hadianawala, Murtuza; Majhi, Sasmita; Mishra, Abhijit; Datta, Bhaskar
Abstract : Hybrid antimicrobials that combine the effect of two or more agents represent a promising antibacterial therapeutic strategy. Abstract : Hybrid antimicrobials that combine the effect of two or more agents represent a promising antibacterial therapeutic strategy. In this work, we have synthesized N -(4-(4-(methylsulfonyl)phenyl)-5-phenylthiazol-2-yl)benzenesulfonamide derivatives that combine thiazole and sulfonamide, groups with known antibacterial activity. These molecules are investigated for their antibacterial activity, in isolation and in complex with the cell-penetrating peptide octaarginine. Several of the synthesized compounds display potent antibacterial activity against both Gram-negative and Gram-positive bacteria. Compounds with 4- tert -butyl and 4-isopropyl substitutions exhibit attractive antibacterial activity against multiple strains. The isopropyl substituted derivative displays low MIC of 3.9 μg mL −1 against S. aureus and A. xylosoxidans . The comparative antibacterial behaviour of drug–peptide complex, drug alone and peptide alone indicates a distinctive mode of action of the drug–peptide complex, that is not the simple sum total of its constituent components. Specificity of the drug–peptide complex is evident from comparison of antibacterial behaviour with a synthetic intermediate–peptide complex. The octaarginine–drug complex displays faster killing-kinetics towards bacterial cells, creates pores in the bacterial cell membranes and shows negligible haemolytic activity towards human RBCs. Our results demonstrate that mere attachment of a hydrophobic moiety to a cell penetrating peptide does not impart antibacterial activity to the resultant complex. Conversely, the work suggests distinctive modes of antibiotic activity of small molecules when used in conjunction with a cell penetrating peptide.